Extreme precipitation induced concurrent events trigger prolonged disruptions in regional road networks - Raviraj Dave; Srikrishnan Siva Subramanian; Udit Bhatia (Environmental Research Letters, 2021)
Concurrency in extreme precipitation-induced events including flooding, landslides and associated debris flow result in massive loss of life, damage to infrastructures, and widespread disruption to socioeconomic activities. Despite recent advances in field of risk hazard modeling, we lack a systematic framework to model and assess the impact of extreme precipitation induced concurrent hazards on infrastructure lifelines including road networks. Here we develop an integrated framework to study the effect of concurrent hazards i.e. landslide, debris flow, and flood on regional road networks. Our spatiotemporal 1D simulations of shallow landslides and debris flows in combination with the 2D hydrodynamic model for floods indicate that even highly localized concurrent events have potential to induce widespread and prolonged disruptions to the regional road networks. We illustrate the proposed framework’s application to assess the functionality loss from the individual and concurrent events induced by extreme precipitation. Our results show that not accounting for concurrence in these correlated hazards could result in underestimation of functionality losses by 71 $%$ , which in turn can undermine the pre-disaster preparedness and post-disaster recovery efforts.